Browning Prevention of Flour from Freshly Harvested Porang (Amorphophallus oncophyllus) Tubers through Immersion in Sodium Metabisulfite at Various Times - Amyranti, Mutia (UNIVERSITAS ISLAM SYEKH - YUSUF TANGERANG, 2020)
Porang (Amorphophallus oncophillus) tubers contain multifunctional water-soluble heteropolysaccharides, called glucomannan. Therefore, the quality of porang tuber chips is highly depending on its glucomannan content and physical appearance. The presence of considerable amount of carotene, polyphenoloxidases and tannins in these tubers may cause browning of flour during processing. The purpose of this research was to study the effect of enzymatic anti-browning agent (sodium metabisulfite) concentrations (2, 5 and 7.5%) w/w) and immersion times (30, 60, 90, 120, 150 and 180 minutes) on the degree of whiteness. An increase in the concentration of anti-browning agent solution up to 5% w/w caused significant increase the degree of whiteness of porang flour and quality of porang flour. However, further increase in the concentration of anti-browning agent solution exhibited reduction in the degree of whiteness and quality of porang flour. In addition, a longer immersion time also resulted in a higher degree of whiteness of porang tuber chips. The best browning prevention conditions were through immersion of porang tuber chips in 7.5% w/w sodium metabisulfite solution for 150 minutes, from which a highest degree of whiteness was achieved (81.99).